Pressure ulcer in frail hospitalized elderly people / Úlcera por presión en ancianos frágiles hospitalizados - Belaunde Clausell, Antonio; Lluis Ramos, Guido Emilio; Consuegra Ivars, Geovanys (Archivos del Hospital Universitario "General Calixto García", 2021)
Full text in English and Spanish. ABSTRACT Introduction: Pressure ulcer is a lesion of ischemic origin produced by prolonged pressure. This entity currently represents an important health problem. Objective: To characterize frail patients with pressure ulcer admitted to "Dr. Carlos J. Finlay" Central Military Hospital in the period between January 2021 and July 2021. Methods: An observational cross-sectional study was carried out. We worked with 105 frail elderly people. The prevalence of pressure ulcer was estimated according to the following variables: age, age group, sex, skin color, schooling, marital status, depth of the lesion, location, patient mobility and continence, presence of diseases, nutritional status, and cognitive impairment. Results: The mean age was 76.9 years. The prevalence of pressure ulcers in frail elderly people was 29.5 % (CI: 21-38.1). There was a predominance of Grade II ulcers (51.6 %; CI: 35.5-70.9) and ulcers of sacral location (38.7 %); CI: 22.6-54.8). Additionally, 86.7 % (CI: 80.5-92.3) had reduced mobility and 23.7 % (CI: 19-38.3) had urinary continence disorders. On the other hand, 61.3 % (CI: 45.2-77.4) of patients who developed pressure ulcer had poor nutrition and 51.6 % (CI: 39.3-68.5) had dementia. Conclusions: The prevalence of pressure ulcers is high in elderly patients admitted to the internal medicine ward. Its prevalence increases with decreased mobility, dementia and poor nutrition. RESUMEN Introducción: La úlcera por presión, es una lesión de origen isquémico, producida por presión prolongada. Esta entidad actualmente representa un importante problema de salud. Objetivos: Caracterizar a los pacientes frágiles con úlcera por presión ingresados en el Hospital Militar Central “Dr. Carlos J. Finlay”, en el período enero de 2021-julio de 2021 Método: Se realizó un estudio observacional, de corte transversal. Se trabajó con 105 adultos mayores frágiles. Se estimó la prevalencia de úlcera por presión según las variables: edad, grupo etario, sexo, color de piel, escolaridad, estado civil, profundidad de la lesión, localización, movilidad del paciente, continencia, presencia de enfermedades, estado nutricional y deterioro cognitivo. Resultados: La edad promedio fue de 76,9 años. La prevalencia de úlceras por presión en ancianos frágiles fue de 29,5 % (IC: 21-38,1). Predominaron las úlceras grado II (51,6 %; IC: 35,5-70,9) y de localización sacra (38,7 %; IC: 22,6-54,8). El 86,7 % (IC: 80,5-92.3) tenía movilidad reducida y el 23,7 % (IC: 19-38,3) tenía trastornos de continencia urinaria. El 61,3 % (IC: 45,2-77,4) de los pacientes con úlcera por presión padecía del malnutrición y el 51,6 % (IC: 39,3-68,5) tenía demencia Conclusiones: La prevalencia de úlceras por presión en ancianos frágiles es alta en adultos mayores ingresados en sala de medicina interna. Su prevalencia aumenta en ancianos con disminución de la movilidad, dementes y con malnutrición.